2018
DOI: 10.1159/000488249
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Diffuse Reflectance Spectroscopy: Non-Erythemal in vivo Testing of Sun Protection Factor

Abstract: Background/Aims: In order to define a label sun protection factor (SPF) of topically applied sunscreens, in vivo test methods like ISO 24444, FDA guideline, or the Australian standard are used worldwide. The basis of all these methods is provoking an erythemal skin reaction by UV irradiation to find the level of unprotected and protected minimal erythemal doses (MED). In vitro methods replacing the human skin by any kind of non-human material are still not available. Thus, offering the new hybrid diffuse refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 16 publications
(11 reference statements)
0
23
0
Order By: Relevance
“…This system comprised a control unit, a lighting unit, and an image acquisition unit. This was a “dual spectral filtering system” that was similar to the double monochromatic system adopted in the HDRS . The UV spectral interference filter sets in the same wavelength range (310‐380 nm in 10‐nm steps) were mounted on both the light unit and the image acquisition unit.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This system comprised a control unit, a lighting unit, and an image acquisition unit. This was a “dual spectral filtering system” that was similar to the double monochromatic system adopted in the HDRS . The UV spectral interference filter sets in the same wavelength range (310‐380 nm in 10‐nm steps) were mounted on both the light unit and the image acquisition unit.…”
Section: Methodsmentioning
confidence: 99%
“…Ruvolo et al proposed a new in vivo SPF assessment method that combined the human skin diffuse reflectance spectra and the in vitro transmittance spectra of sunscreen material . Rohr et al demonstrated that hybrid diffuse reflectance spectroscopy (HDRS) provided great SPF estimation accuracy for a huge variety of sunscreen materials ( R 2 = 0.973 for 80 materials in a wide formulation) . However, because these methods require contact examination of a particular skin site, in situ spatiotemporal evaluation is difficult.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, as shown in Table , there are differences in the definitions of the labeled SPF classification between these protocols. Furthermore, in recent years, some new in vivo methods based on reflectance spectroscopy have been investigated to protect ethical concerns of UV‐induced damages on volunteers but all of them are not accepted as a new standard until now …”
Section: Sun Protection Factor (Spf)mentioning
confidence: 99%